2011
DOI: 10.1159/000334712
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Phytotherapy in Neonatology

Abstract: Background: There is an enormous economical significance of phytotherapy at least in Germany, the huge demand of patients was repeatedly proven. Simultaneously data exist for different application areas and ages as for younger children and pregnancy until birth. The actual neonatal period can be of interest because phytotherapy is used in younger children and until birth, it is not very likely that there is a gap in this period of life. Aim: To give an overview on the current literature on phytotherapy in neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Given the high power of our study (86.5%), we consider our results reliable. None of the prior aromatherapy studies performed in infants have described any side effects, for instance nausea, vomiting or chills [22,25,27,38]. In keeping in line with them, we also have observed no side effects from its use.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Given the high power of our study (86.5%), we consider our results reliable. None of the prior aromatherapy studies performed in infants have described any side effects, for instance nausea, vomiting or chills [22,25,27,38]. In keeping in line with them, we also have observed no side effects from its use.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies concluded that the use of a familiar odor (mainly breast milk, but also vanillin, present in VEO) helps to reduce agitation, apneas, and stress and adverse effects of neonatal pain [27,35,36]. Vanillin seems to be hedonically pleasant for full-term and preterm neonates, seems to in uence pain reaction, and may even be analgesic, especially if the infant has been previously exposed to its odor [26,27,33,37]. We did not sensitize neonates with the aroma of VEO because we performed the frenotomy when it was indicated, and thus there was no time to sensitize them prior to the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies concluded that the use of a familiar odor (mainly breast milk, but also vanillin, present in VEO) helps to reduce agitation, apneas, and stress and adverse effects of neonatal pain [29,37,38]. Vanillin seems to be hedonically pleasant for full-term and preterm neonates, seems to influence pain reaction, and may even be analgesic, especially if the infant has been previously exposed to its odor [28,29,35,39]. We did not sensitize neonates with the aroma of VEO because we performed the frenotomy when it was indicated, and thus, there was no time to sensitize them prior to the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There are cases where the amount of α wave with higher frequency values increase during olfactory stimulation [7]. However, because of its effect in the human state of mind, the aromas are used in medicine [8], phytotherapy [9], and aromatherapy [10].…”
Section: Introductionmentioning
confidence: 99%